A risk communication model for food regulatory agencies in modern society. Issue 1 (September 2015) - Charlebois, Sylvain; Summan, Amit
<x xml:space="preserve">Abstract</x> It is important for the Canadian Food Inspection Agency (CFIA) and other food regulatory bodies to recognize that risk communication is a key component of the quality risk assessment process for which problems of subjectivity and uncertainty may arise. This paper develops a core risk communication strategy, motivated by a risk communication model, for food safety regulators. The model specifies communication strategies directed at consumers and the food industry as well as evaluation and continuous improvement processes. The risk communication strategy will minimize the effects of food safety risks by influencing stakeholder behaviour, improve overall interactions between the food regulatory agency and relevant stakeholders, and strengthen food safety risk prevention and mitigation systems.